Material didáctico "CONTEXTUALIZADO" y su Influencia en el aprendizaje de la comprensión Lectora de los estudiantes de cinco años de la Institución Educativa inicial Nº 231 del distrito de Rioja - Pérez Becerra, Alicia (2006)
In the initial level worry re-dresses the process of education learning of the communicative capacities since they are the key for other learnings that the education offers. The difficulties in the development of these capacities it is a problem, which solution is in diagnosing the reasons that give him(her) origin, considering and executing alternatives of solution, task that relapses into the hands of the teachers. The educational materials facilitate the learnings of the children (seize) and they consolidate the saberes with major efficiency. They stimulate the function of the senses and the previous learnings, to accede to the information, to the development of capacities and to the formation of activities and values. From this perspective there has been realized the investigation which aim(lens) has been to systematize the Material Didactic Contextualizado, whose aplicabilidad improves the learning of the reading comprehension of the five-year-old students of the Educational lnstitution N º 231 of the district of Rioja, in the year 2006. The contributions of Ausubel, Piaget and Vigotsky, who emphasize the conception of to educate, focused from the learning that supposes activity, significatividad and functionality of the learned; besides the contributions of the interactive character of the reading, sustained in the psicolingüística and the cognitive psychology, base to the investigation, which is orientated to demonstrate the following hypothesis: The didactic material contextualizado will influence significantly in the learning of the reading comprehension of the five-year-old students of the Educational lnstitution N° 231 of the district of Rioja, in the year 2006. The investigation of type applied, experimental level, quasiexperimental design of preprueba - it(he,she) posttries, has been taken to end by a population equal sample to 16 children and 5-year-old girls of the-Educational lnstitution of the lnitial Level N° 231 of the sector Atahualpa, of the district of Rioja. To the above mentioned children he(she) administered a test(proof) of reading comprehension, befare and after the execution of classes using the Material Oidactic Contextualizado. From 16 students there have been gathered the information, which tried with the comparison of averages and variances of pairecf punctuations there has demonstrated the acceptance of the alternate hypothesis. Being fulfilled that tc = 10,25> tt = 1,753; it(he,she) is to say, tcƐRRɅɇRA therefore H1 : μA> μB. Then the alternate hypothesis is accepted and pushes the void one back. In consequence the Material Didactic Contextualizado has influenced significantly in the learning: of the reading comprehension of the five-year-old students of the Educational lnstitution N ° 231 of the district of Rioja, in the year 2006.